Innovation as A Strategy of Agrowical Competition Advantage in Improving Marketing Performance of Luwak Coffee Products in Gianyar Bali - Pande Ketut Ribek; I Gede Rihayana (AIBPM Publisher, 2019)
Agro tourism is a place for nature-based creativity and packaged in the form of trips or tourism activities to plantations or agriculture. One of them is luwak coffee agro tourism. This agrotourism has an icon of luwak coffee as a mainstay product in attracting tourists and increasing sales. Through a study entitled